Material for Strengthening of Entrance Edges of Work Blades of Stream Turbines - Glushkova, D.B.; Grinchenko, E.D.; Kostina, L.L.; Demchenko, S.V.; Ryzhkov, Yu.V. (Металлофизика и новейшие технологии, 2017)
The influence of electrode material on the state of build-up layer of steam turbine rotor blades is investigated. The strengthening layer is formed by means of the electrospark alloying with use of alloy Т15К6 and steel 15Х11МФШ. Microstructure, microhardness, and thickness of build-up layer are investigated. The advantages of steel 15Х11МФШ for the strengthening of leading edges of steam turbine rotor blades are substantiated.